'It's on video, every second of it': a micro-sociological analysis of cycle rage. Issue 3 (2nd July 2016) - Lloyd, Mike
Abstract : A case study is presented of a violent incident that arose between two men riding a mountain biking track in New Zealand. This gained both local and international attention after one of the riders posted his video of the incident on a social media site where it went 'viral'. The video helped identify the other rider, who was taken to trial and convicted of assault. The fairness and means of the conviction is not at issue here, rather, the interest is in the video as a rare record of the joint production, in real time, of an ordinary trouble that takes an unexpected turn. The two riders catch up with each other, travelling downhill at a decent speed on a narrow track. Their riding requires significant concentration, nevertheless, while biking they are able to communicate, verbally and visually. This communication shows disagreement about the format of their riding-together, with the camera-clad rider wanting to pass the older rider in front, and proceed at a faster pace. Except for an intriguing and brief interlude, however, the older rider will not let the other pass. Consequently, the camera-clad rider grows increasingly frustrated, but the problem is he is oblivious to the way his own tailgating affects the rider in front. It is the tailgating, along with some 'lecturing', that annoys the older rider. At the end of the ride both stop, complaints and accusations are made, then a brawl breaks out. Adapting Katz's (1999) work on emotions, we see both riders doing being 'pissed off', but with one shifting to 'being done' by his anger, escalating into violence. Screensnaps and transcriptions from the video are used to analyse the fine detail of a 5-minute mountain bike gone wrong.